2020
DOI: 10.3390/foods9040486
|View full text |Cite
|
Sign up to set email alerts
|

Classification and Authentication of Paprika by UHPLC-HRMS Fingerprinting and Multivariate Calibration Methods (PCA and PLS-DA)

Abstract: In this study, the feasibility of non-targeted UHPLC-HRMS fingerprints as chemical descriptors to address the classification and authentication of paprika samples was evaluated. Non-targeted UHPLC-HRMS fingerprints were obtained after a simple sample extraction method and C18 reversed-phase separation. Fingerprinting data based on signal intensities as a function of m/z values and retention times were registered in negative ion mode using a q-Orbitrap high-resolution mass analyzer, and the obtained non-targete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Variables with <30% relative standard deviation of the QC were retained for further multivariate data analysis. Unsupervised principal components analysis (PCA) and supervised partial least squares discriminant analysis (PLS-DA) ( Barbosa et al, 2020 ) clustering methods were run on GC-MS data in Simca-P software v14.0 (Umetrics AB, Umeå, Sweden) 6 . Unit variance scaling was used in PCA and orthogonal projections latent structures discriminant analysis (OPLS-DA).…”
Section: Methodsmentioning
confidence: 99%
“…Variables with <30% relative standard deviation of the QC were retained for further multivariate data analysis. Unsupervised principal components analysis (PCA) and supervised partial least squares discriminant analysis (PLS-DA) ( Barbosa et al, 2020 ) clustering methods were run on GC-MS data in Simca-P software v14.0 (Umetrics AB, Umeå, Sweden) 6 . Unit variance scaling was used in PCA and orthogonal projections latent structures discriminant analysis (OPLS-DA).…”
Section: Methodsmentioning
confidence: 99%
“…The proposed UHPLC-HRMS-based strategy achieved the goal, reaching a classification rate of 80.9%. A similar work was conducted by Barbosa et al [10], who coupled UHPLC-HRMS with PLS-DA in order to discriminate the same classes of paprika. The metabolomic fingerprint, coupled with PLS-DA, resulted in a suitable strategy, leading to a correct classification rate of 100%.…”
Section: Discussion Over the Comparison Of The Outcome With The Literaturementioning
confidence: 93%
“…Unlike detection of adulterants (illegal artificial colorants or bulking agents), false origin labelling or contamination of origin-certified spices with low-quality products cultivated elsewhere cannot be unveiled by conventional targeted analytical methods due to the lack of specific markers directly related to the product origin [6]. Various fingerprinting or profiling methods, based on vibrational spectroscopies [7,8], high-or ultrahigh-performance liquid-chromatography coupled to different detector systems [9][10][11][12], and energy dispersive X-ray fluorescence [13], have been proposed to identify the origin of bell pepper spices. In this context, it has been found that the profiles of phenolic acids, polyphenolic compounds and capsacinoids are promising indicators for geographical traceability purposes.…”
Section: Introductionmentioning
confidence: 99%
“…As an established method, PCA has recently been used as an exploratory approach, for example, in LC-MS-based authenticity studies to distinguish tissue origin of bovine gelatin [ 164 ], for the differentiation of the geographical origin of peppers [ 165 ] and pork [ 166 ]. However, PCA was always used together with another supervised method to identify clear differences.…”
Section: From Non-targeted Data Sets To Marker Compoundsmentioning
confidence: 99%